Form and function in Greek grammar : linguistic contributions to the study of Greek literature - Rijksbaron, Albert, (Amsterdam Studies in Classical Philology, 2018)
Albert Rijksbaron is internationally known as one of the leading scholars of the Ancient Greek language, whose work has exerted a strong and lasting influence on the scholarly debate concerning many aspects of Greek linguistics. This volume brings together twenty of his papers, two of which have been translated into English and some which are not easily accessible elsewhere. The selection represents the full range of Rijksbaron's research, including papers on central topics in Greek linguistics such as tense-aspect, mood, voice, particles, negation, the article, questions, discourse analysis, as well as on the views of ancient grammarians and modern commentators. As a whole, the volume shows how much linguistic analysis can contribute to our understanding of Greek literary texts.